Holding Distribution Channel Relationships Together: The Role of Transaction-Specific Assets and Length of Prior Relationship - Weiss, Allen M.; Kurland, Nancy (Organization Science, 1997)
The authors investigate the effect of managers' perceptions of two types of transaction-specific investments on their intention to terminate a current interorganizational relationship: (1) the specific knowledge necessary for a manufacturer's representative (rep) to carry out the selling function for a given manufacturer and (2) the specific knowledge reps acquire about their own customer accounts. The extent to which the length of prior relationship strengthens or weakens the hypothesized linkages is also examined. The authors test the hypotheses within the context of distribution channels (i.e., between a manufacturer and its selling agent), which are characteristic of many vertical organizational relationships. The results replicate in an additional setting some prior findings on the influence of transaction-specific investments between two parties directly involved in a relationship. The authors also find that specialized investments by a downstream partner (i.e., a manufacturer's rep) in relationships that are even farther downstream (i.e., customer accounts) can influence a manufacturer's intention to terminate the manufacturer-rep relationship. Moreover, the length of prior relationship between a manufacturer and its rep is shown to moderate this effect.